Apoptosis : pharmacological implications and therapeutic opportunities - Kaufmann, Scott H. (Advances in pharmacology (San Diego, Calif.), 1997)
Programmed cell death (PCD) has become a topic of widespread interest and experimentation over the past decade. Written by experts in the field, Apoptosis: Pharmacological Implications and Therapeutic Opportunities concentrates on presenting an overview of PCD pathways as they are currently understood, and strives to identify important unanswered questions as well as other therapeutic possibilities suggested by recent biochemical discoveries. Understanding the biochemical pathways that participate in the cell death process has become an important goal in developmental biology, neurobiology, cardiology, and infectious disease research. The control of apoptosis has also become a major area of investigation in the field of cancer biology. Apoptosis: Pharmacological Implications and Therapeutic Opportunities contains an overview for those with a general interest in apoptosis, and provides discussions of sufficient depth to be useful for specialists in the field.